A1.19 Altered distribution of innate lymphoid cell populations in human LYMPH node biopsies obtained during the earliest phases of systemic autoimmunity. (24th February 2016) - Hähnlein, JS; Rodriguez-Carrio, J; Ramwadhdoebe, TH; Semmelink, JF; Choi, IY; van Lienden, KP; Maas, M; Gerlag, DM; Tak, PP; Geijtenbeek, TBH; van Baarsen, LGM
Abstract : Background and objective: Innate lymphoid cells (ILCs) emerge as important mediators of immunity and accumulation of inflammatory ILC populations has been reported in various inflammatory-mediated conditions. We investigated the frequency and distribution of ILCs in lymph node biopsies obtained during the earliest phases of rheumatoid arthritis (RA). Materials and methods: Twelve patients with early rheumatoid arthritis (RA), 12 individuals positive for autoantibodies but without arthritis (RA-risk group) and 7 healthy controls underwent ultrasound-guided inguinal lymph node biopsy. Frequencies of ILCs subsets as well as the expression of VCAM and ICAM by lymph node endothelial cells and fibroblasts were analysed by flow cytometry. Results: Although no difference in the number of total ILCs (Lin - CD45 + /low CD127 + ) was found among the three study groups, the distribution of the different ILC populations changed. RA patients showed a relative lower frequency of LTi (c-Kit + NKp44 - ILCs) and an increased frequency of ILC1 (c-Kit - NKp44 - ILCs) and ILC3 (c-Kit + NKp44 + ILCs) populations compared with controls (p < 0.001, p < 0.05 and p < 0.05, respectively). RA-risk individuals showed a relative increased frequency of inflammatory ILC1 compared with controls (p < 0.01). Frequencies of LTi correlated with the expression of adhesion molecules on endothelial and fibroblastic cells. Conclusions: Already during the earliest phases of systemic autoimmunity, the ILC distribution in lymph nodes changes from a homeostatic towards a more inflammatory profile, thereby supporting a role for ILCs in the pathogenesis of RA.